PENGARUH MOTIVASI KERJA TERHADAP KINERJA GURU BAHASA INDONESIA DI SMK NEGERI 1 TOMA - Wau, Rosni (Universitas Nias Raya, 2025)
The problem in this research is that there are still teachers who lack discipline in the learning process and there are still teachers who neglect their work. The aim of this research is to determine the effect of work motivation on the performance of Indonesian language teachers at SMK Negeri 1 Toma for the 2023/2024 academic year. This type of research is quantitative research. The subjects in this research were 2 Indonesian language teachers at SMK Negeri 1 Toma for the 2023/2024 academic year. The results of the research show that there is a significant influence between work motivation and teacher performance as evidenced by the value of work motivation (X) t count 1 > t table 0.997 with a significance level of 0.05 (5%) with a very strong correlation coefficient, which means that work motivation (X) has a positive effect on teacher performance (Y), then Ha which states if t count > t table = Ha is accepted and t count < t table = Ha is rejected. So, the value of Ha is accepted. The suggestions put forward by the researcher are suggestions to school leaders to always provide better teacher performance, and can be used as reference material and information material for readers and advanced researchers and raise the same problem in the future.